ANALISIS PEMETAAN MUTU PENDIDIKAN SMP NEGERI 3 BOJA KABUPATEN KENDAL - Rias Dewi Setyowati; Titik Haryati (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2025)
This research aims to describe the mapping analysis of the quality of education at SMP Negeri 3 Boja, Kendal Regency. The research approach used is qualitative. This type of research is a case study. This research uses triangulation of sources and methods. Data analysis in three steps: data reduction, presenting data, and drawing conclusions. The results of the research show that: Mapping the education report card of SMP Negeri 3 Boja, it can be concluded that this school has several strengths that can be the basis for improving the quality of education, such as a high student graduation rate, basic competencies that have been mastered by the majority of students, as well as active participation in learning. However, there are also several weaknesses that need attention, such as disparities in learning outcomes in several subjects, limited infrastructure, and the need to increase teacher competency to support innovative learning. For this reason, data-based strategic steps are needed, such as developing remedial programs, increasing training for teachers, and optimizing the use of technology in learning.